2008
DOI: 10.1016/j.fertnstert.2007.05.074
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of microRNA species in human uterine leiomyoma versus normal myometrium

Abstract: Our findings indicate that miRNAs are differentially expressed between human leiomyoma and matched myometrium. Given this differential expression, miRNAs may play a role in the pathogenesis of uterine leiomyoma and may serve as future therapeutic targets for the treatment of these tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(108 citation statements)
references
References 27 publications
5
99
0
3
Order By: Relevance
“…In cultured human uterine cell lines, we also showed that the high level of endogenous RECK protein was downregulated by miR-21 in HeLa cells, whereas the low level of endogenous RECK protein was up-regulated by the miR-21 inhibitor in Ishikawa cells. These data showed that RECK was not only the target gene of miR-21, but the endogenous RECK protein level was also regulated by miR- 21.…”
Section: Confirmation and Comparison Of Mirna Microarray Data-mentioning
confidence: 83%
“…In cultured human uterine cell lines, we also showed that the high level of endogenous RECK protein was downregulated by miR-21 in HeLa cells, whereas the low level of endogenous RECK protein was up-regulated by the miR-21 inhibitor in Ishikawa cells. These data showed that RECK was not only the target gene of miR-21, but the endogenous RECK protein level was also regulated by miR- 21.…”
Section: Confirmation and Comparison Of Mirna Microarray Data-mentioning
confidence: 83%
“…A number of studies have been conducted to perform profiling and function analyses of miRNAs in human uterine leiomyoma using microarray and deep sequencing. 82,[127][128][129] These studies demonstrate that many miRNAs regulating cellular processes including cell proliferation, apoptosis, cell adhesion, WNT signaling, mitogen-activated protein kinase (MAPK) signaling, nuclear factor kB (NF-kB) activation, and insulin signaling are deregulated in leiomyoma when compared to normal tissues. Importantly, the predicted targets of these deregulated miRNAs including let-7, miR-21, miR-23b, miR-29b, and miR-197 in leiomyoma play an important role in the pathogenesis of leiomyoma.…”
Section: Dysregulation Of Mirna In Uterine Leiomyomamentioning
confidence: 99%
“…Follow-up studies demonstrate abnormal global genomic methylation in UL compared to normal myometrium [Yamagata et al 2009], implicating possible epigenetic contributions to genetic susceptibility of UL development. Several miRNAs such as let7, miR-21, miR-93, miR-106b, and miR-200 are significantly deregulated in UL cells compared to normal myometrium [Marsh et al 2008]. Growing evidence indicates that steroid hormones E2 and P are the most important epigenetic regulators of growth factors, cytokines, chemokines, and extracellular matrix components that are so important for UL progression.…”
Section: Epigenetic Regulation Of Ulmentioning
confidence: 99%